O patrimônio cultural em Sergipe sob a lente do poder judiciário: análise da jurisprudência no Tribunal de Justiça de Sergipe e no Tribunal Regional Federal da 5ª região - Ramos, Lucilla Menezes da Silva (2019)
The dissertation analyzes the jurisprudential production on cultural heritage in Sergipe at the Court of Justice of Sergipe - TJ / SE - and in the Federal Regional Court of the 5th Region - TRF-5ª -, with the hypothesis that both the TJ / SE and the TRF-5ª , when interpreting the current legislation regarding cultural heritage, act in the construction and maintenance of the cultural rights constitutionally guaranteed to all. The judgments were searched in the eletronic addresses of the respective courts, with a time frame of 30 years, between 1989 and 2018. The broad temporal cut of the research developed here, after the Federal Constitution of 1988, aims precisely to perceive, from the outset of a new democratic order in Brazil, as the Judiciary is positioned when it is called to act in demands that deal with the cultural patrimony, understanding the reasons explained in the judgments and the discursive amplitude referring to the subject of the culture coming from the concrete interpretation proposed by the courts. In this context, the general objective is to verify what are the arguments used by the Sergipe Court of Justice and the Federal Regional Court of the 5th Region in the trial of the cultural heritage lawsuits, trying to understand if there is any decision-making standard in such demands. The specific objectives, in turn, are to verify the decision coherence in the spatial and temporal context chosen; to produce an explanation of the meaning of the decisions based on the interpretation of the decision-making process, the form of the decisions and the arguments produced. It also seeks to investigate the existence or not of conflicts between doctrine, legislation and judicial decisions regarding the subject. In addition, the methodology adopted favors bibliographical and documentary research in the analysis of scientific articles, doctrine, legislation and jurisprudence, and, in relation to the exposition of the theme, it is emphasized that it is guided by deductive reasoning, starting from the most general aspects to the most specific, starting with the exposition of elementary concepts for the understanding of the thematic to later enter the jurisprudential analysis.